2014
DOI: 10.3758/s13423-014-0772-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cognitive load on delayed recall

Abstract: Recent studies have suggested that long-term retention of items studied in a working memory span task depends on the refreshing of memory items-more specifically, on the number of refreshing opportunities. However, it was previously shown that refreshing depends on the cognitive load of the concurrent task introduced in the working memory span task. Thus, cognitive load should determine the long-term retention of items assessed in a delayed-recall test if such retention relies on refreshing. In two experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
83
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 20 publications
18
83
2
3
Order By: Relevance
“…These restoration processes can be argued to not only protect representations in WM from decay but to also help establishing long-term memory traces. Whereas articulatory maintenance rehearsal has only a limited effect on long-term memory (Greene, 1987), refreshing has been shown to improve long-term retention (Raye et al, 2007), and providing more time for refreshing during a WM task results in better recall of the memoranda in a delayed test (Camos & Portrat, 2015;Loaiza & McCabe, 2012b) Therefore, the efficiency of refreshing could be a source of common variance of WM and long-term memory. In line with this hypothesis, Loaiza and McCabe (2012a) have argued that age differences in episodic long-term memory can in part be explained by age differences in the efficiency of refreshing.…”
Section: Correlations With Long-term Memory (C3)mentioning
confidence: 99%
“…These restoration processes can be argued to not only protect representations in WM from decay but to also help establishing long-term memory traces. Whereas articulatory maintenance rehearsal has only a limited effect on long-term memory (Greene, 1987), refreshing has been shown to improve long-term retention (Raye et al, 2007), and providing more time for refreshing during a WM task results in better recall of the memoranda in a delayed test (Camos & Portrat, 2015;Loaiza & McCabe, 2012b) Therefore, the efficiency of refreshing could be a source of common variance of WM and long-term memory. In line with this hypothesis, Loaiza and McCabe (2012a) have argued that age differences in episodic long-term memory can in part be explained by age differences in the efficiency of refreshing.…”
Section: Correlations With Long-term Memory (C3)mentioning
confidence: 99%
“…Focusing briefly on an item enhances its level of activation and thus counteracts memory loss. It has been suggested that these two classic maintenance mechanisms, operating independently on the maintenance of verbal information, affect different features of the memoranda , Camos & Portrat, 2015.…”
Section: Wm Maintenance Mechanisms Contributing To Recall Performancementioning
confidence: 99%
“…New associations are formed between elements concurrently held in the focus of attention resulting in new LTM information that is formed during short-term memory tasks: a chunk. The information that benefits from attentional refreshing may be in a more deeply analyzed form (Cowan & Chen, 2009) and more persistent (Camos & Portrat, 2015) than information that is activated without the involvement of the focus of attention, that is, by articulatory rehearsal. Hence, associations or links between elements, that is, chunks, are stored as a specific function of the focus of attention (Cowan, 1999(Cowan, , 2001(Cowan, , 2005a(Cowan, , 2005b and the focus of attention would be limited to a few chunks at a time (usually three to five chunks in adults; see Cowan, 2001).…”
Section: Wm Maintenance Mechanisms Contributing To Recall Performancementioning
confidence: 99%
“…Bernardin, & Camos, 2004;Barrouillet, Bernardin, Portrat, Vergauwe, & Camos, 2007;Barrouillet, Portrat, & Camos, 2011;Camos & Portrat, 2015;Hudjetz & Oberauer, 2007;Ricker & Cowan, 2010;Vergauwe, Barrouillet, & Camos, 2009; but see Oberauer, Lewandowsky, Farrell, Jarrold, & Greaves, 2012;Oberauer & Lewandowsky, 2013), and (2) increasing the number of times a memory item has been refreshed, by presenting cues prompting participants to think of specific WM items during a retention interval, results in better memory performance for that item (Souza, Rerko, & Oberauer, 2015). In these studies, researchers have focused on the effects of refreshing on memory performance at the end of the trial or at the end of the experimental session.…”
mentioning
confidence: 99%